Hermeneutics and Nihilism. Meaning, Agency, and the Dialectics of Negativity in Gadamer’s Thought - Ilia Inishev (Phainomena)
Nihilism, as a pervasive destructive tendency that permeates all aspects of modern life, is rooted in an established perceptual stance characterized by the dominance of a particular kind of agency. Philosophical hermeneutics is arguably the most suitable approach to provide both a comprehensive diagnosis and an effective remedy. Its diagnostic and therapeutic potentials are linked to its notion of the meaningful, which is not distilled from an experience laden with material, bodily, and other “contaminations,” but rather coincides with the radical—and, in this sense, normative—self-disclosure of the livable, or truly human, world. In this article, I examine the potential of Gadamerian hermeneutics for revealing and disseminating forms of agency that offer alternatives to the destructive attitudes deeply embedded in contemporary cultures.